Shigeru ban : - Ban, Shigeru (TOTO, 2017)
Rising architecture star Shigeru Ban designs and builds graceful structures using organic materials such as paper tubes, bamboo, and engineered wood. He has designed projects at both ends of the client spectrum, from one-room temporary houses for earthquake refugees to private seaside and urban villas, and has won widespread praise for his humanitarian efforts and innovative use of recyclable, affordable materials as well as for his poetic architectural style. This book, designed in collaboration with the architect, presents his projects in sections - paper, wood, bamboo, prefabrication, and skin - that delineate the major themes of his work, accompanied by technical information that documents Ban's pioneering tests on these materials.